Seasonal nitrogen remobilization and the role of auxin transport in poplar trees. (12th March 2020) - Li, Gen; Lin, Rongshoung; Egekwu, Chioma; Blakeslee, Joshua; Lin, Jinshan; Pettengill, Emily; Murphy, Angus S; Peer, Wendy A; Islam, Nazrul; Babst, Benjamin A; Gao, Fei; Komarov, Sergey; et al.
Abstract : This study establishes a role for poplar bark storage protein catabolism and N remobilization to shoot growth following dormancy, and a regulatory role for auxin in seasonal N remobilization. Abstract: Seasonal nitrogen (N) cycling in Populus, involves bark storage proteins (BSPs) that accumulate in bark phloem parenchyma in the autumn and decline when shoot growth resumes in the spring. Little is known about the contribution of BSPs to growth or the signals regulating N remobilization from BSPs. Knockdown of BSP accumulation via RNAi and N sink manipulations were used to understand how BSP storage influences shoot growth. Reduced accumulation of BSPs delayed bud break and reduced shoot growth following dormancy. Further, 13 N tracer studies also showed that BSP accumulation is an important factor in N partitioning from senescing leaves to bark. Thus, BSP accumulation has a role in N remobilization during N partitioning both from senescing leaves to bark and from bark to expanding shoots once growth commences following dormancy. The bark transcriptome during BSP catabolism and N remobilization was enriched in genes associated with auxin transport and signaling, and manipulation of the source of auxin or auxin transport revealed a role for auxin in regulating BSP catabolism and N remobilization. Therefore, N remobilization appears to be regulated by auxin produced in expanding buds and shoots that is transported to bark where it regulates protease gene expression and BSP catabolism.